Пасхальность русской словесности - Есаулов Иван Андреевич (Кругъ, 2004)
Экземпляры: ФИЛ (20050714) / Инвентарный номер: 1053225 / Цена: 40.00 / Сис.шифр: 83.3(2=Рус) / Авт.знак: Е 81 / ГРНТИ: 17 / ББК: 83.3(2=Рус)-02